Effect of corporate risk disclosures on firm value of listed firms in Kenya - Ang'edu, E. (Strathmore University, 2024)
Listed corporations in Kenya encounter internal and external hurdles that jeopardize their competitive edge over the years, resulting in distressed cases, decline in share price, and in severe situations, entire destruction of value, resulting in delisting. The Nairobi Securities Exchange has witnessed significant growth in recent years, but there are questions about the market setting a premium on the deliberate efforts of information asymmetry and corporate governance practices. The general objective of the study is to investigate the effect of corporate risk disclosure on firm value of entities trading at the NSE. The research was supported by the Efficient Market Hypothesis theory, Signaling theory and the Agency theory. The study followed a positivist philosophy focused as it attempts to establish findings from the study variables by empirically demonstrating the influence and effect corporate risk disclosure has on NSE listed entities in Kenya. The study utilized secondary data acquired by content analysis from annual audited reports of 64 NSE listed corporations over 2015-2022. SPSS version 25 and Stata version 18 was used for the balanced panel data analysis in the descriptive statistics, regression analysis, and diagnostic tests employed. The regression results reveal a negative and statistically significant effect of corporate risk disclosure on firm value. This research adds to literature by presenting the findings of an emerging capital market in a developing country and recommends further can adopt further reports like integrated annual reports that will bring out more disclosures and risk statements. Further studies can adopt additional regression models with different type of dataset, have additional control variables and use other measures of firm value like Market to book value to provide a supplementary viewpoint on the relationship between risk disclosure and firm value.
Full - text thesis